UPAYA MENINGKATKAN MINAT DAN HASIL BELAJAR MAHASISWA PENDIDIKAN MATEMATIKA DENGAN PENERAPAN MEDIA WIZER.ME PADA MATA KULIAH GEOMETRI DATAR DAN RUANG - I Made Surat; I Dewa Putu Juwana; I Komang Sukendra (LP3M Universitas PGRI Mahadewa Indonesia, 2025)
Learning outcomes are a reflection of the learning process that students have gone through, but in reality there are still many students who are not motivated to practice working on mathematics problems. This study aims to determine the increase in students' interest and learning outcomes in the Flat and Spatial Geometry course through the application of interactive learning media Wizer.me. The subjects of this study were 3rd semester students of the Mathematics Education Study Program in the 2024/2025 academic year. This study uses the Classroom Action Research (CAR) method which is carried out in two cycles. Each cycle consists of the planning, implementation, observation, and reflection stages. Data collection techniques include interviews, learning outcome tests, learning interest questionnaires, and documentation. Data sources come from lecturers and students. Data analysis is carried out quantitatively and qualitatively. The results of the study showed an increase in both student interest and learning outcomes. Learning interest in cycle I reached 62.5% and increased to 80% in cycle II. Student learning outcomes also increased, from an average pre-cycle score of 60 with 50% completion, to 78 with 75% completion in cycle I, and increased again to 84 with 100% completion in cycle II. Thus, it can be concluded that the use of Wizer.me media can increase students' interest and learning outcomes in the Flat and Spatial Geometry course in the Mathematics Education Study Program, Universitas PGRI Mahadewa Indonesia.